English Teachers’s Readiness in Implementing Deep Learning Approach at the Elementary School Level - Ivan Ananta Luckita; Dewi, Puspa; Triana, Juita (Scripta : English Department Journal, 2025)
English education in elementary schools is crucial for equiping students with early communication skills in the global era. The Indonesian education curriculum continues to develop, including the implementation of a deep learning approach that is believed to improve students' critical thinking, problem-solving, and collaboration skills. This study analyzes the readiness of elementary school English teachers on the southern coast of Central Java and Yogyakarta to implement deep learning in learning activities. The instrument in this study was an interview containing eighteen questions that had to be answered by fourteen elementary school English teachers. The results show that teachers have a positive understanding of this approach and implement it through methods that are relevant to student conditions, interesting media, and the use of technology. However, increasing the English teachers’ readiness is still needed through training and workshops, especially for teachers without an English education background.